Management of open apex in maxillary incisors with mta - a retrospective study - PRIADARSINI T,; SOWMYA K,; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
Open apices commonly arise secondary to pulpal necrosis as a result of caries or trauma in an immature tooth with incomplete root formation. The conventional method of apexification with calcium hydroxide has certain disadvantages such as a very long period of treatment, tooth fracture and an incomplete calcification of the bridge. MTA has gained importance as an alternative treatment for management of open apices as it overcomes these disadvantages. The aim of this study was to determine the number, age and gender distribution of MTA apexification done in maxillary incisors.This study included data of 41 patients who had undergone apexification using MTA in maxillary incisors. The data was collected from the case records of patients visiting Saveetha dental College for treatment. A total of 47 teeth that underwent MTA apexification were identified. Of the total subjects, 83% were males and 17% were females. 51.06% of the teeth that underwent MTA apexification belonged to the age group <15 years and 48.04% to the group >15 years. Statistical analysis was done using IBM SPSS software version 20.0. No significant association was found between gender and different age groups in patients that underwent MTA apexification (P value- 0.701 >0.05; Fisher’s exact test). MTA apexification was done predominantly in males in both age groups.